Analisa Koordinasi Proteksi Relay Jarak Dengan Software Digsilent Pada Gi Sukolilo Ke Gi Kenjeran Menggunakan Metode Fuzzy - Misbahul Munir; Novian Patria Uman Putra; Wahyu Setyo Pambudi; Nasyith Hananur Rohiem; Ipung Nur Ifan (BEES: Bulletin of Electrical and Electronics Engineering, 2022)
The electromagnetic distance relay at the Sukolilo substation has been replaced with a digital relay equipped with a recloser. If there is a disturbance, the relay will trip and reconnect automatically. The setting values have changed as a result of this replacement. The purpose of this study was to determine the value of the distance relay setting at the Sukolilo substation using traditional calculations, which would then be implemented in a computer program developed by PLN Ltd. It also found out the results of calculations per zone included in the distance relay zone. This study employed a fuzzy method with digsilent software. The research data comprised data on SUTT installed at the Sukolilo substation, data on conductor relay settings at the Sukolilo substation, data on short circuit currents, and transformer ratios. The simulation results in this study indicated that the distance relay had a setting value that was not in accordance with the standard in the old setting of the Sukolilo substation zone 1 for protection (175.42%), while the calculation results showed that zone 1 protected 58.44%. The new impedance setting covered zone 1 = 0.338, zone 2 = 0.862, and zone 3 = 1.488, whereas the old impedance setting showed zone 1 = 0.1126, zone 2 = 0.2924, and zone 3 = 0.4128. The old setting time and the new setting showed a big difference in that the old setting time was 0.25 seconds with a range of 175.42% while the new setting time was 0.25 seconds with a range of 58.44%.